Tat Twam Asi Based Role-Playing Learning Model in Social Studies Knowledge Competence - Agustini, Kadek Dwi Intan; Suarjana, I Made; Jayanta, I Nyoman Laba; Renda, Ndara Tanggu (International Journal of Elementary Education, 2020)
The low competence of Social Studies knowledge possessed by students due to lack of active students in the learning process. This is one of the reasons this research was conducted. This study aimed at examining the impact of Tat Twam Asi based Role-Playing learning model on the mastery of Social Studies competence. This was a quasi-experiment study and the design was an on-equivalent post-test only control group. The population in this study were all grade V ofÂ  Gugus IV elementary school Buleleng Sub-district, Buleleng regency, amounting to 5 classes with a total of 172 students. The samples were students ofÂ  SD Negeri 1 Banyuasri as an experimental group with a total of 35 students and SD Negeri 5 Banyuasri as a control group of 32 students determined by applying group design random sampling technique. Data on the competence of Social Studies knowledge were collected by using multiple-choice tests. Descriptive statistics and inferential statistics are t-tests polled variants were applied in analyzing them. After analyzing the data, the t-count is 8,99 while the t-table is 3.99, so the t-count is greater than the t-table. This shows that there are differences in the mastery of IPS knowledge competence between the experimental group and the control group. Based on the findings, it could be concluded that Tat Twam Asi based role play learning model had a significant impact on the mastery of Social Studies knowledge competence. This model can be chosen by the teacher as an alternative in the learning process activities to achieve the expected learning objectives.